Analisis Resepsi Remaja Pada Adegan Lesbian Dalam Series Sianida (Episode 1) (E-Jurnal Medium, 2022)
Lesbians are one of the homosexual phenomena, lesbian are women who have an interest in other women. In Indonesia in 2021, there will be a series that focuses on lesbian cases, namely the cyanide series. This study aims to determine the meaning of teenagers in the lesbian scene contained in the cyanide series (episode 1), this study targets Denpasar teenagers with an age range 18 – 24 years and who have watched the cyanide series. This study uses the receprion theory decoding and encoding from Stuart Hall with the analysis of Stuart Hall’s Reception Analysis. The type of research used is descriptive – qualitative. This study involved six informants. The results of analysis in the study indicate that four people fall into the Dominan Position, and two people fall into the Oppositional Position. Keywords: Reception Analysis, Teenagers, Lesbian Scene, Cyanide Series (Episode 1)